Adaptation of Radiology Software to Improve Cardiology Results Reporting - Webster, Gregory; Ward, Kendra; Deal, Barbara J.; Anderson, Jeffrey B.; Tsao, Sabrina (Applied Clinical Informatics, 2017)
Objective: Twenty-four hour ambulatory electrocardiograms (“Holter” monitors) are a key diagnostic test in cardiology. Commercial electronic medical record (EMR) tools have not been designed for pediatric Holter monitor reporting and paper-based methods are inefficient.Methods: Our tertiary pediatric hospital adapted a radiology EMR tool to a cardiology workflow in order to report Holter monitor results. A retrospective review was performed at 4 time points: prior to intervention, immediately post-intervention, at 6 months and at 12 months post-intervention. The primary outcome variable was time to reporting of Holter findings.Results: Holter reports were reviewed on 527 studies (patient ages: 1 day to 42 years). The time between the date the patient returned the Holter monitor until the date the referring physician received a final report improved from 19.8 days to 1.5 days (p<0.001). This result was durable over the next 12 months of follow-up. Physician interpretation time improved from 2.1 days to 0.6 days (p=0.01). Transcriptionist time and result scanning time were eliminated (removing 1.9 days and 14 days from the workflow, respectively).Conclusion: EMR systems are not typically designed for pediatric cardiology, but existing systems can be adapted, yielding important gains for patient care. In specialties like pediatric cardiology, there is insufficient volume nationally to drive development of commercial systems. This study demonstrates the general principle that creative adaptation of EMR systems can improve result reporting in pediatric cardiology and likely in other cardiology practices.Citation: Webster G, Ward K, Deal BJ, Anderson JB, Tsao S. Adaptation of Radiology Software to Improve Cardiology Results Reporting. Appl Clin Inform 2017; 8: 936–944 https://doi.org/10.4338/ACI-2017-03-RA-0051
Keywords: Pediatrics; Ambulatory care information systems; Electronic Health Records; Clinical Care; Quality Improvement